Structural (AMS), petrological and geochemical (Rb-Sr, Sm-Nd, U-Pb) studies of the african negash and konso plutons (Ethiopia) : significance of Mafic-Felsic magma interactions to the construction of calc-alkaline plutons - (:unkn) unknown (My University, 2002)
This multidisciplinary work has two major objectives: (i) understanding the structures and textures related to solidification of mafic-felsic magma interactions (mixing and mingling) and their implications ta mechanisms of magma emplacement and pluton construction and (ii) understanding the geodynamic and temporal relationships between two major structures of the Pan-African orogeny in Northeast Africa which met in Ethiopia : the ArabianNubian Shleld (ANS) and the Mozambique Belt (MB). based on a comparative study of Negash (ANS) and Konso plutons (MB). Malic-felsic interactions. Two major types of mafic-feisic magma interactions characterize the Negash pluton: (i)mingling and mixing at the lower mafic-felsic interfaces and (il) strongly mixed and mingled monzodiorites. Structural,mineralogical and chemical data suggest that the pluton was construcled by a successive assemblage of four differentiated magma batches (at intermediate chambers), which were forcefully injectedinto pre-existing foliatedcountry rocks and that the different types of hybridisation are not random but are related ta the dynamics and mechanismof pluton emplacement: (i) monzogranitic followed by granodioritic magmas; (ii) injection of a malt-richmonzodioritic/monzogabbroic tangue into the partially crystaliized felsic magmas resulting in inverted density gradient which in tum led to interactions at the lower interfaces; and (iii) simultaneous rising of granodioritic and monzodioriticmagmas along the same conduit resulting in the strongly hybridised magma which represents the last intrusion. The hybrid rocks are not results of simple binary mixing but involve atleast three end-members (monzoqabbres,monzodiorites and monzogranites/granodiorites). All these data suggest emplacement of differentiated, low viscosity magma batches and that the pluton was constructed by an assembly of successive melt-rich catches (dyking)ANS and MS. The ANS, which is composed of calc-alkaline and juvenile
Keywords: African Research